Role of oral corticosteroids with adjunct to intravenous antibiotics in treatment of orbital cellulitis - Shah, Sangeeta; Lavaju, Poonam; Gupta, Mukesh Kumar; Pokharel, Shailesh Mani; Chaudhary, Sanjib Kumar; Chaudhary, Santosh (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: The standard treatment protocol of orbital cellulitis includes the use of broad-spectrum intravenous antibiotics. This study was done to evaluate the role of oral corticosteroids in the treatment of orbital cellulitis in order to address the inflammatory component. Methods: A prospective comparative interventional study was carried out on 17 cases of orbital cellulitis over 16 months. All the patients were treated with intravenous antibiotics and were allotted to Group A or B. The former consisted of eight cases (intravenous antibiotics) while group B consisted of nine cases (intravenous antibiotics and oral corticosteroids). The oral corticosteroids were started after 24 to 48 hours of initiation of antibiotics. The outcomes compared between the two groups were hospital stay, visual analogue score, temperature, peri-orbital edema, proptosis, visual acuity, extra-ocular movement and conjunctival chemosis. Results: The age of the participants ranged from 7 to 77 years with M:F = 6:11. The mean duration of hospital stay was 7.75±2.7 and 8.22± 2.53 days in group A and B. The result showed that the changes in the other parameters were significant on the 3rd day after starting treatment in both groups but insignificant between the groups at the end of 7th and 14th day. Conclusions: In our study, addition of oral corticosteroids to intravenous antibiotics showed no added beneficial effect over the use of intravenous antibiotics alone in the treatment of orbital cellulitis. However, it was noted that there was no further deterioration of the disease with the use of steroids.